The Dendrimers as Drug Delivery Platforms of the Mechanisms, Benefits, and Use in Anti-Pain: Systematice Literature Review: Drug Delivery Platforms - Yusiana Wahyudi, Najla; Rahayu, Sri (STIKes Mandala Waluya Kendari, 2024)
Background: Efforts to reduce the side effects of long-term NSAID use have prompted exploration of transdermal drug delivery, which offers advantages such as avoiding first-pass metabolism, reducing pain, allowing sustained drug release, and improving patient compliance. Dendrimers, specifically polyamidoamine (PAMAM), are attracting attention for their potential in drug delivery. PAMAM has a three-dimensional structure of monodisperses with high amino group density and internal voids suitable for drug encapsulation. Methods: This research method uses the literature review method which begins with the collection of journals to be reviewed. The article search was conducted on the Pubmed database. Researchers searched with the keyword dendrimer. The two main synthesis methods are convergent and divergent dendrimers. Results: : Drug molecules can be trapped in dendrimers through hydrogen, hydrophobic, or electrostatic bonds. The advantages of dendrimers include improved solubility, permeability, and targeted drug delivery, while the disadvantages are high cost, toxicity and aggregation. This system has been used in several pain medications. Conclusions: Dendrimers are macrostructures with unique characteristics such as nanoscopic size, multifunctional surface, and high branching, making them ideal as drug delivery systems. Ketoprofen with PAMAM-type dendrimers showed that PAMAM dendrimers could significantly increase the accumulative amount of permeation of both drugs after 24 hours, compared with the drug suspension without PAMAM dendrimers. Dendrimers are multi-branched monodisperse macrostructures, derived from Greek.